The Effect of Environmental Performance, Corporate Social Responsibility Disclosure, and Independent Commissioners on Financial Performance - Pryobudi Purbosanjoyo; Anindita Pratiantrie; Tashia Egidia (Jurnal Akuntansi Trisakti, 2018)
The objective of this research was to examine the effect of environmental performance, CSR disclosure, and size of Independent Commissioners towards financial performance. The population of this research comprises companies registered as Manufacturing Consumer Goods listed at Indonesia Stock Exchange. Purposive sampling is used to determine the sample with an observation period 2015-2017. This study uses secondary data derived from annual reports and financial statements. Data analysis using a Multiple Linear Regression Analysis. Research results show environmental performance, corporate social responsibility disclosure, and size of independent commissioners together had a relationship to all financial performance measurement namely Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM). CSR disclosure partially has a positive effect to financial performance, whereas environmental performance and size of independent commissioners have no effect to financial performance.